(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Self-regulated learning (SRL) has emerged as a pivotal factor in developing academic writing skills, particularly in higher education settings. This meta-analysis synthesizes empirical findings on the relationship between SRL strategies and academic writing performance. Drawing on social cognitive theory and Zimmerman’s SRL framework, the article examines the effectiveness of goal setting, self-monitoring, and metacognitive regulation across diverse educational contexts. The analysis reveals that SRL strategies consistently enhance writing outcomes by fostering autonomy, cognitive engagement, and motivation. Practical implications for instruction and assessment in academic writing courses are discussed, emphasizing the integration of SRL training into curriculum design to improve learners’ writing proficiency and academic success.